2002
DOI: 10.1051/apido:2002010
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy in routine quality analysis of honey

Abstract: -Fourier-transform infrared spectroscopy (FT-IR) was used as a rapid, simple and reliable method for quality analysis of honey. More than 1600 samples of honey were analysed using FT-IR and reference methods to develop a partial least-square regression based calibration model for the major components of honey (sugars, proline, free acids, invertase, moisture, hydroxymethylfurfural, pH and electrical conductivity). The coefficient of determination R 2 ranging from 0.84-0.98 indicates an acceptable calibration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 10 publications
0
25
1
2
Order By: Relevance
“…In this case more data with higher variability would be needed in order to try to improve the calibration model, similarly to what other authors found for other spectroscopic techniques [34,35]. The RPD for cross-validation and test set validation was higher than 3.7 and ranged from 3.7 (cross-validation for electrical conductivity) to 31.7 (Test-Set for total phenol content).…”
Section: Tablementioning
confidence: 56%
See 1 more Smart Citation
“…In this case more data with higher variability would be needed in order to try to improve the calibration model, similarly to what other authors found for other spectroscopic techniques [34,35]. The RPD for cross-validation and test set validation was higher than 3.7 and ranged from 3.7 (cross-validation for electrical conductivity) to 31.7 (Test-Set for total phenol content).…”
Section: Tablementioning
confidence: 56%
“…This supports the importance of a spectroscopy model in quality control laboratory to quickly point out a low quality honey sample. Lichtenberg-Kraag et al [34] also found good calibration models for the analytical parameter of honey (sugars, proline, free acids, invertase, moisture, HMF, pH and electrical conductivity) analysed using Fouriertransform infrared spectroscopy (FT-IR) and partial least-square regression. The coefficient of determination found by this author ranging from 84% to 98%.…”
Section: Tablementioning
confidence: 97%
“…Near Infrared spectroscopic (NIR) results correlate well with optical activity (Garcia Alvarez et al, 2002), as well as with moisture, fructose, glucose, sucrose and maltose content (Qiu et al, 1999;Pierard et al, 2000). Mid-infrared spectroscopy (MIR) was successfully applied for the determination of fructose, glucose, sucrose, maltose and erlose, electrical conductivity, pH value and free acidity (Lichtenberg-Kraag et al, 2001). Using the same method, invertase activity, moisture, proline and HMF content could not be accurately measured.…”
Section: Determination Of Routine Honey Parameters By Infrared Spectrmentioning
confidence: 99%
“…The results demonstrate that mid-infrared spectrometry is a valuable, rapid and non-destructive tool for the quantitative analysis of honey. More than 1600 samples of honey were analysed using FT-IR and reference methods to develop a partial least-square regression based calibration model for the major components of honey (sugars, proline, free acids, invertase, moisture, hydroxymethylfurfural, pH and electrical conductivity) [Lichtenberg-Kraag et al, 2002]. Fourier-transform infrared spectrometer was used to determine botanical origin of 144 samples of nine different unifloral honey types from different Croatian regions [Svečnjak et al, 2011].…”
Section: Spectroscopic Analysis Of Honeymentioning
confidence: 99%